ANALISIS PENILAIAN KINERJA BANK SYARIAH BERDASARKAN INDEKS MAQASID SHARI'AH (Studi Kasus pada 9 Bank Umum Syariah di Indonesia Tahun 2015) - Sudrajat, Anton; Sodiq, Amirus (Universitas Islam Negeri Sunan Kudus, 2016)
To assess if the aims of Islamic banking establishment has been appropriated with maqashid syariah, this assessment needs performance measurement based on maqashid syariah that was adopted from Abu Zahrah’s concept of maqashid syariah. This article aims to analyze the performance measurement of syariah commercial banks in Indonesia based on maqashid syariah index. This research results the rating of syariah commercial banks as follows: 1) Bank Panin Syariah, 2) BCA Syariah, 3) bank Muamalat, 4) Bukopin Syariah, 5) BRI Syariah, 6) BNI Syariah, 7) Bank Syariah Mandiri, 8) Maybank Syariah, 9) Bank Mega Syariah.